RANGANATHAN VS GORMAN: TINJAUAN ATAS PERKEMBANGAN FIVE LAWS OF LIBRARY SCIENCES - Mafar, Fiqru (Universitas Lancang Kuning, 2011)
Not many studies have been done to focus on figures and their thoughts wich are published in library science. In this writing, the writer will present a comparison on Ranganathan's and Gorman's thoughts dealing with